Lean manufacturing strategy for the implementation in manufacturing enterprises in developing countries. - Zargun, Shibani (Cranfield University, 2016)
Manufacturing organisations all over the world are constantly seeking continuous improvement initiatives to enhance performance and meet customer requirements. In this regard, many manufacturing initiatives have been introduced, one of the most successful and famous process improvement initiatives is Lean Manufacturing based on Toyota Production System (TPS). Lean manufacturing has internationally been proven as an effective approach for reducing many types of waste and creating value for customers. Although many organisations have realised the benefits of lean, many attempts have not been successful to adopt it effectively. Lean manufacturing can lead to improve an organisation's performance, yet implementation’s challenges do exist. Implementing lean in a systematic way is not a simple job and becomes difficult to sustain. While some organisations stumble through with trial and error to achieve a level of leanness, others reply on repeated Kaizen (continuous improvement). The aim of this study was to develop a customised strategy to introduce lean to manufacturing enterprises in developing countries. The developed lean manufacturing transformation strategy (LMTS) encompasses all lean human and technical-related critical success factors. Several research methods have been employed in this research. It included structured questionnaire, semi-structured interviews, and plant observations conducted within three companies in the automotive sector in Libya. The Libyan automotive industry has been used in this research as a representation of the situation in the manufacturing enterprises in similar developing countries. The findings of this study indicated that the managerial and operational practices within Libyan companies are not supportive toward adopting lean manufacturing successfully. Libyan companies lack the infrastructure for lean and their readiness level is comparatively low. The proposed LMTS is aimed to assist organisations in developing countries view lean strategically as a management philosophy rather than as a set of tools and thus guides those organisations toward the initiative's successful adoption. The LMTS will work as a guide for manufacturing organisations in Libya and other relevant developing countries as they proceed toward high impact adoption of lean manufacturing practices.
Keywords: Lean manufacturing; developed countries; developing countries; critical success factors (CSF); leanness; measurement; strategy